Development and use frame of programme management system for organization - Siti Sarah Malini Bt Mohd Hanifa; Rasmaliza Bt Rashid; Zubaidah Bt Abdul Rahman (Journal of Counseling and Educational Technology, 2022)
The frame of Programme Management System for organization is an online system which has basic functions to manage information about certain program. These include courses, workshop or event, participant’s information such as attendance, as well as generating document, for example certification of attendance and report for organization. In fulfilling problem statement for attendance, it is not available since it cannot be administered face to face due to pandemic Covid’19. Next, it is costly to print certificate for participants and it also involved postage cost. Lastly, difficulty in getting the updated list of participants. The objectives of this project are to design, develop and implement an online system in real situation. Methodology used is Prototype, whereby the developing of system is simultaneously administered with the implementation. In conclusion, this project helps organization to run programmes smoothly.